Silver-Loaded Xerogel Nanostructures for Iodine Capture: A Comparison of Thiolated versus Unthiolated Sorbents - Riley, Brian J.; Chong, Saehwa; Marcial, José; Lahiri, Nabajit; Bera, Mrinal K.; Lee, Sungsik; Wu, Tianpin; Kruska, Karen; Matyáš, Josef (ACS applied nano materials, 2022)
This paper describes the development and provides comparisons of thiolated (−SH) and unthiolated Ag–Al–Si–O xerogels for iodine gas capture. These xerogels were produced from alkoxides and then heat-treated at 350 °C to provide mechanical strength for subsequent processing steps. Then, a portion of the xerogels was thiolated using (3-mercaptopropyl)trimethoxysilane. Next, thiolated and unthiolated batches were ion-exchanged in AgNO3 solutions where Ag+ replaced Na+ in the gel network on a near 1:1 molar basis. Subsamples of the Ag-exchanged xerogels were subjected to a reduction step in H2/Ar to convert Ag+ to Ag0 where the rest of the Ag-exchanged (Ag+) were not reduced. X-ray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy revealed nanoscale Ag0 in the Ag+ samples despite no active reduction where actively reduced samples had bimodal Ag0 distribution of ∼2–3 nm hexagonal and ∼6–7 nm cubic crystallites. Synchrotron X-ray absorption spectroscopy was used to assess the oxidization states of Ag, S, and I within the different xerogel samples. The specific surface areas of the base xerogels decreased as subsequent treatments were performed on the as-made samples, albeit the decreases were smaller than aerogel equivalents of these samples from a previous study. All iodine-loaded Ag-based samples showed a mixture of β-AgI and γ-AgI. Comparisons of iodine-loading results with other Ag-based iodine sorbents show that the thiolated Ag0-xerogels in this work have one of the highest iodine-loading capacities (q e) reported to date in saturated conditions with the thiolated Ag0-xerogel showing 522 mg iodine per g of the sorbent.